Integrating Approach to Build Customer Experiences: Lessons Learned from Mobile Customers in Ghana - Yiadom, Michael Boakye; Tait, Madéle (Journal of Economics and Behavioral Studies, 2021)
Delivering a great customer experience is of paramount importance for any organization. The better experience customers have regarding the organization’s products, or brands, the more repeat purchases and positive reviews they will receive. This paper explores the mobile mix as an integrated approach to facilitate a positive customer experience. A total of 415 respondents were selected and completed the survey through stratification and convenient sampling from10 regions. The study adopted a positivistic paradigm and followed a quantitative research approach. The SPSS Amos 25 was utilized to analyze the collected data. The empirical results revealed that the mobile service mix has a significant positive influence and relationship with customer experiences. This paper provides relevant and practical recommendations that could increase positive customer experiences in the mobile industry.